HUBUNGAN KECEMBURUAN DAN KONTROL DIRI PADA PELAKU DATING VIOLENCE - Afsari Ramadita; Naomi Soetikno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Based on the Annual Record of the National Commission on Violence Against Women in 2023, it states that cases of dating violence in dating relationships top the list. Quantitative research methods are used with purposive sampling techniques, the research sample consists of 295 young adult respondents (aged 20-30 years) who have experienced dating violence. The research tool used the Multidimensional Jealousy Scale (MJS) to estimate the level of jealousy and the Self Control Scale (SCS) to assess self-control. The use of the Spearman correlation test was chosen because the data were not normally distributed based on the results of the normality test. The results showed that there was a negative and significant relationship between jealousy and self-control (rho = -0.186, p < 0.05). This shows that the higher the level of jealousy, the lower the level of self-control in dating violence perpetrators. The analysis used the Spearman correlation test because the normality test showed that the data were not normally distributed. The results showed a negative and significant relationship between jealousy and self-control.